Early inflammatory response in soft tissues induced by thin calcium phosphates. Issue 9 (30th July 2013) - Rydén, L.; Molnar, D.; Esposito, M.; Johansson, A.; Suska, F.; Palmquist, A.; Thomsen, P.
Abstract : The inflammatory response to titanium and hydroxyapatite (HA)‐coated titanium in living tissue is controlled by a number of humoral factors, of which monocyte chemoattractant protein‐1 (MCP‐1) has been specifically linked to the recruitment of monocytes. These cells subsequently mature into tissue‐bound macrophages. Macrophages adhering to the proteins adsorbed at the implant surface play a pivotal role in initiating the rejection or integration of the foreign material. Despite this, little is known about the initial inflammatory events that occur in soft tissues following the implantation of titanium and HA‐coated titanium implants. In this study, circular discs of commercially pure titanium (c.p. Ti) with either a thin crystalline HA coating or amorphous HA coating or uncoated were implanted subcutaneously into rats. The implants were retrieved after 24 and 72 h. The lactate dehydrogenase (LD) activity, DNA content, expression of MCP‐1, interleukin‐10 (IL‐10), tumor necrosis factor α (TNF‐α), as well as monocyte and polymorphonuclear granulocyte counts in the exudate surrounding the implants were analyzed. There were significantly higher DNA and LD levels around the titanium implants at 24 h compared with HA‐coated titanium. A rapid decrease in MCP‐1 levels was observed for all the implants over the period of observation. No statistically significant differences were found between the two HA‐coated implants. Our results suggest a difference in the early soft‐tissue response to HA‐coated implants when compared with titanium implants, expressed as a downregulation of inflammatory cell recruitment. This suggests that thin HA coatings are promising surfaces for soft tissue applications. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 2712–2717, 2013.